One-dimensional van der Waals material SbPS4 with large bandgap for UV sensing applications - Cho, Sooheon; Zhang, Xiaojie; Lee, Bom; Kang, Jinsu; Jeong, Byung Joo; Kim, Dahoon; Kim, Yeong Hyeop; Park, Jae Hyuk; Kim, Sang Hyuk; Yu, Hak Ki; Choi, Jae Young (Sensors and Actuators A: Physical, 2024)
UV sensors possess high importance for modern electronics such as environmental monitoring, health diagnostics, and optoelectronic devices. Thus UV-sensing-materials with high stability has drawn significant interest for next generation UV sensors. Herein, a simple synthesis method of SbPS4 has been proposed. Then the SbPS4 crystals are effectively delaminated by micromechanical exfoliation into a few-nanometer-scale nanowires, which is the first demonstration of the material's possibility of exfoliation down to one-molecular-layer thickness. Weak van der Waals (vdW) interaction within the crystal lattice can be easily overcome. The exfoliated SbPS4 nanowires showed one-dimensional tube structure, and the work function of SbPS4 showed strong thickness dependence and was confirmed through Scanning Kelvin probe microscopy. The bandgap of 2.54 eV of SbPS4, showed great sensitivity to UV lights, depicting SbPS4 as a promising future UV sensing material for future optoelectronic application.
Keywords: Diagnostic device; Environmental Monitoring; One-dimensional; One-dimensional van der waal material; Scanning Kelvin probe microscopy; Sensing applications; Sensing material; UV sensor; UV-sensing; Van der Waal; One-dimensional van der Waals material; SbPS4; Scanning Kelvin probe microscopy; UV sensor